Customized Loading of microRNA-126 to Small Extracellular Vesicle-Derived Vehicles Improves Cardiac Function after Myocardial Infarction - Bheri, Sruti; Brown, Milton E.; Park, Hyun Ji; Brazhkina, Olga; Takaesu, Felipe; Davis, Michael E. (ACS Nano, 2023)
Small extracellular vesicles (sEVs) are promising for cell-based cardiac repair after myocardial infarction. These sEVs encapsulate potent cargo, including microRNAs (miRs), within a bilayer membrane that aids sEV uptake when administered to cells. However, despite their efficacy, sEV therapies are limited by inconsistencies in the sEV release from parent cells and variability in cargo encapsulation. Synthetic sEV mimics with artificial bilayer membranes allow for cargo control but suffer poor stability and rapid clearance when administered in vivo. Here, we developed an sEV-like vehicle (ELV) using an electroporation technique, building upon our previously published work, and investigated the potency of delivering electroporated ELVs with pro-angiogenic miR-126 both in vitro and in vivo to a rat model of ischemia-reperfusion. We show that electroporated miR-126+ ELVs improve tube formation parameters when administered to 2D cultures of cardiac endothelial cells and improve both echocardiographic and histological parameters when delivered to a rat left ventricle after ischemia reperfusion injury. This work emphasizes the value of using electroporated ELVs as vehicles for delivery of select miR cargo for cardiac repair.
Keywords: Bilayer membranes; Cardiac functions; Cardiac repair; Extracellular; Extracellular vesicle; Ischemia-reperfusion injury; Mir-126; Myocardial Infarction; Nanovesicle; Vesicle engineering; Animals; Endothelial Cells; Extracellular Vesicles; Ischemia; MicroRNAs; Myocardial Infarction; Rats; Extracellular vesicle; ischemia-reperfusion injury; miR-126; myocardial infarction; nanovesicle; vesicle engineering